2020
DOI: 10.1007/s10554-020-02014-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and morphological changes of carotid kinking and coiling in growth: an echo-color Doppler study of 2856 subjects between aged 0 to 96 years

Abstract: Extracranial internal carotid artery (EICA) kinking and coiling are the most frequently reported carotid anomalies in the literature. Embryogenic and acquired causes for such anomalies have been postulated but the prevalence of kinking and coiling has not been well characterized across age categories. The aim of this study is to evaluate the prevalence of EICA coiling and kinking among different age groups to better understand its potential causes and changes during the course of life. A total of 2856 subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
19
0
9

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 20 publications
0
19
0
9
Order By: Relevance
“…We found that age and the duration of hypertension are independent risk factors for carotid artery tortuosity, while the use of antihypertensive drugs is a protective factor against carotid artery (3,20,24,25). With age, the elastic layer of blood vessels degenerates and breaks, and their integrity is destroyed.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…We found that age and the duration of hypertension are independent risk factors for carotid artery tortuosity, while the use of antihypertensive drugs is a protective factor against carotid artery (3,20,24,25). With age, the elastic layer of blood vessels degenerates and breaks, and their integrity is destroyed.…”
Section: Discussionmentioning
confidence: 83%
“…In previous studies, the incidence rate of carotid artery tortuosity ranged from 4 to 87% ( 3 , 12 , 20 ). The incidence rate in this study was 63.6%, and such a large difference in the incidence rates across different studies may be due to the following reasons.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…5 In another study by Di Pino et al, the prevalence of carotid artery anomalies among adults and children did not exceed 9.9%. 6 It is known that DICA can be asymptomatic, but most often presents with hemispheric symptoms. Since this pathology is not well understood, there is no consensus among clinicians about the effectiveness of a particular type of Keywords ► bilateral ► cerebrovascular insufficiency ► dolichoarteriopathy ► internal carotid artery ► stroke ► surgery ► results…”
mentioning
confidence: 99%
“…5 In another study by Di Pino et al, the prevalence of carotid artery anomalies among adults and children did not exceed 9.9%. 6…”
mentioning
confidence: 99%